Form and Facade Study on Mixed-Use Office Centre SQ Residence: A Contemporary Architectural Approach - Aldi Fadilah; Andiyan Andiyan; Wanda Yovita; Dian Kusbandiah; Risma Viantara (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
This study aims to analyze the form and façade of the SQ Residence mixed-use office center in Jakarta, Indonesia, in the context of contemporary architectural principles. The focus is on identifying visual and geometric characteristics that reflect modern design in an urban setting. A qualitative descriptive method was employed, combining a literature review of architectural theories with direct field observations. Data were collected through documentation and visual analysis, focusing on external elements due to access limitations. The SQ Residence office center, consisting of three identical towers, features an elliptical base form with additive and subtractive transformations that create a dynamic and expressive mass. The façade integrates glass panels for transparency and natural light, combined with a secondary skin of steel and aluminum composite panels, forming vertical and horizontal rhythmic patterns. These features align with key aspects of contemporary architecture: innovative geometry, contrasting materials, transparency, and contextual distinction. The design of the SQ Residence office center demonstrates how contemporary architecture can effectively merge aesthetic expression with environmental and urban responsiveness. This study contributes to the understanding of form-façade relationships in mixed-use developments and highlights practical design strategies for architects working in dense urban environments.